Sovereign Climate Debt Instruments : An Overview of the Green and Catastrophe Bond Markets - Ando, Sakai; Fu, Chenxu..; Roch, Francisco; Wiriadinata, Ursula (Washington, D.C. : International Monetary Fund, 2022)
Financial markets will play a catalytic role in financing the adaptation and mitigation to climate change. Catastrophe and green bonds in the private sector have become the most prominent innovations in the field of sustainable finance in the last fifteen years. Yet, the issuances at the sovereign level have been relatively recent and not well documented in the literature. This Note discusses the benefits of issuing these instruments as well as practical implementation challenges impairing the scaling-up of these markets. The issuance of these instruments could provide an additional source of stable financing with more favorable market access conditions, mitigate the stress of climate risks on public finances and facilitate the transition to greener low-carbon economies. Emerging market and developing economies stand to benefit the most from these financial innovations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt Management; Debt; Foreign Exchange; Informal Economy; Underground Econom